The Indonesian copula adalah: What it is (not) and why we do (not) need it - Dominik Besier (Nusa, 2021)
This paper addresses the structural status, function, and predictability of the Indonesian copula adalah. It is analyzed as a non-verbal element that is realized in T. Nevertheless, adalah does not behave like a T-auxiliary as it is not sensitive to movement. Therefore, adalah is analyzed as a post-syntactic operation at the phonological form interface. The main functions of adalah are to help identify the break between the subject and predicate, and to act as an element for a smooth intonation contour. A full prediction of adalah remains impossible as its occurrence is influenced by factors such as register, communication setting, participating speakers, etc. Nevertheless, it is possible to identify environments where adalah is unlikely, namely when there is no need for prosodic smoothening or disambiguation, mostly due to overt strategies such as T-auxiliaries, particles, or topicalization/focalization.